Effect of an AI‐based chatbot on students' learning performance in alternate reality game‐based museum learning - Liang, Hsin‐Yi; Hwang, Gwo‐Jen; Hsu, Tien‐Yu; Yeh, Jen‐Yuan (British journal of educational technology, 2024)
Recently, alternate reality games (ARGs) have been applied in museum learning to encourage learners' active engagement through playful problem‐solving activities. However, most learners have insufficient prior knowledge and metacognitive skills to complete the learning tasks in such games. To support learning with ARGs, there is a need to provide proper feedback so that the learners are capable of self‐regulated learning and solving the problems encountered during the learning process. Considering the influences of individual differences, this research developed a chatbot as a learning partner in ARG‐based learning to support students’ learning with adaptive feedback in a museum. A quasi‐experimental study was conducted to evaluate the effectiveness with and without the proposed approach. The results showed that the AI‐based chatbot approach could significantly improve learners' metacognition awareness, emotional engagement and behavioural engagement. Besides, it is helpful to facilitate students' double‐loop learning.Practitioner notesWhat is already known about this topic Alternate reality games (ARGs) enable students to interact with real‐world contexts. The complexities of real contexts and ambiguities of the ARGs could frustrate students and demotivate their engagement in problem‐solving activities. Conventional corrected feedback may fail to match individual students' requirements in solving encountered problems. What this paper adds An AI‐based chatbot was designed as a smart learning partner to support the students in solving encountered problems. The experimental results showed that the proposed approach improved students' metacognitive awareness and engagement. A drawing analysis and a behaviour sequential analysis were applied to further examine the students' perceptions and behavioural patterns. Implications for practice and/or policy It is potentially worth integrating AI‐based chatbots into game‐based learning to promote students' metacognitive awareness and engagement. AI‐based chatbots provide adaptive feedback to effectively facilitate students' self‐regulated learning and double‐loop learning.